2012
DOI: 10.4049/jimmunol.1201413
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: B Cells Are Essential for Protective Immunity against Salmonella Independent of Antibody Secretion

Abstract: Typhoid fever and non-typhoidal bacteremia caused by Salmonella remain critical human health problems. B cells are required for protective immunity to Salmonella but the mechanism of protection remains unclear. Here, we immunized WildType, B cell deficient, antibody-deficient and class-switched antibody-deficient mice with attenuated Salmonella and examined protection against secondary infection. As expected, WildType mice were protected and B cell deficient mice succumbed to secondary infection. Interestingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
62
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 36 publications
(48 reference statements)
5
62
0
Order By: Relevance
“…This has established both antibody-dependent and -independent roles for B cells in acquired immunity against Salmonella. The antibody-independent function of B cells in acquired Salmonella immunity in the mouse seems to represent a critical role for B cells in the development of protective T H 1 CD4 + T cells responses, with B cell-deficient but not antibody-deficient mice exhibiting impaired Salmonella-specific IFNγ production in CD4 + T cells following vaccination 102 . Interestingly, these antibody-independent effects seem to dominate the protective effects of B cells in acquired Salmonella immunity 102 .…”
Section: X-linked Hyper Igm Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…This has established both antibody-dependent and -independent roles for B cells in acquired immunity against Salmonella. The antibody-independent function of B cells in acquired Salmonella immunity in the mouse seems to represent a critical role for B cells in the development of protective T H 1 CD4 + T cells responses, with B cell-deficient but not antibody-deficient mice exhibiting impaired Salmonella-specific IFNγ production in CD4 + T cells following vaccination 102 . Interestingly, these antibody-independent effects seem to dominate the protective effects of B cells in acquired Salmonella immunity 102 .…”
Section: X-linked Hyper Igm Syndromementioning
confidence: 99%
“…The antibody-independent function of B cells in acquired Salmonella immunity in the mouse seems to represent a critical role for B cells in the development of protective T H 1 CD4 + T cells responses, with B cell-deficient but not antibody-deficient mice exhibiting impaired Salmonella-specific IFNγ production in CD4 + T cells following vaccination 102 . Interestingly, these antibody-independent effects seem to dominate the protective effects of B cells in acquired Salmonella immunity 102 . This may, in part, explain why human primary immunodeficiencies characterized by antibody deficiency provide little evidence of a specific susceptibility to invasive Salmonella disease.…”
Section: X-linked Hyper Igm Syndromementioning
confidence: 99%
“…Therefore, it is conceivable that Salmonella-specific CD4 ϩ T cells may be required for the initiation of a B cell-mediated response against Salmonella and B cells may influence Salmonella-specific T cell responses (68). Such a model does not explain why B cell-deficient mice are capable of clearing a primary infection if the same B cell-T cell interactions are an important component of bacterial clearance.…”
Section: Discussionmentioning
confidence: 90%
“…This hypothesis is supported by the fact that CD28 Ϫ/Ϫ mice produce very low levels of Salmonella-specific IgG1, IgG2a, or IgG2b antibodies (65,66). Although the present study and others have shown that mice deficient in B cells clear a primary infection with an attenuated strain just as well as C57BL/6 mice (33, 34), protection against a secondary lethal infection with wild-type Salmonella critically depends on the presence of B cells (33,34,67) but not antibodies (68). Interestingly, B cells can be infected by Salmonella in vivo and in vitro (69,70), and B cells can present Salmonella antigens to T cells (69).…”
Section: Discussionmentioning
confidence: 96%
“…Both CD4 and CD8 T cells contribute to the resolution of primary Salmonella infection, while CD4 T cells play a dominant role in providing secondary protective immunity (16)(17)(18). The role of B cells is more complex, since this cell population is not required for primary clearance but contributes to secondary protective immunity via antibody-dependent and antibody-independent mechanisms (19)(20)(21)(22). In order to survive within an immunocompetent host, Salmonella has evolved multiple mechanisms to combat innate and adaptive immune responses (23)(24)(25)(26).…”
mentioning
confidence: 99%